The determination of heavy metal content in soil treated with high dosage of fertilizer in paddy / Salwa Ibrahim - Ibrahim, Salwa (Faculty of Plantation and Agrotechnology, 2016)
This study is about research to determine heavy metal content treated with high dosage of fertilizer in soil planted with paddy. Many source of heavy metal in soil such as achieve high yield farmers used many kind of fertilizer , pesticides and fungicide . The uncontrolled dosage of fertilizer can contribute many problems such as excessive heavy metal environment problem. It's also can cause toxicity and decrease fertility. This study wants to determine whether high dosage fertilizer can be a factor of soil contamination. The objective of this study are to determine the heavy metal content in soil planted with paddy before applying fertilizer and to determine the relationship of heavy metal content after applying fertilizer. The samples were extracted for their total nutrient content by wet digestion method. As a result, for before and after Cu there are significant different (p<O.05) on treatment 3 only. For before and after Zn there are significant on treatment 1 and 3.The fertilizers were applied cause the amount of heavy metal in soil change.